ON ANOMALOUS DIELECTRIC FUNCTION OF INTERSTELLAR GRAIN IN FAR INFRARED - Altman, I. S.; Pikhitsa, P. V. (Одеські астрономічні публікації, 2017)
We show that the fact that the thermal radiation from small particles follows the Wien law instead of the Planck one should lead to the anomalous wavelength dependence of the far-infrared emission efficiency of interstellar grain substance. We claim that photoconductivity of interstellar grains induced by the ultraviolet radiation from a hot star may account for this dependence.